Management of pulmonary arterial hypertension in patients aged over 65 years - Sitbon, Olivier (Eur Heart J Suppl, 2019)
Historically, pulmonary arterial hypertension (PAH) has been considered a disease of young adults, but over the last three decades, the average age at diagnosis has increased, presenting clinicians with some unique challenges. Clinical symptoms of PAH, including shortness of breath and reduced functional capacity, are not specific for the disease and may be present in older patients because of their age or as a result of comorbid conditions. Eliminating other causes for these symptoms can delay PAH diagnosis and initiation of PAH-specific treatment compared with younger patients. Currently, there are no specific guidelines relating to PAH in older patients and existing guidelines for identifying patients at potential risk of PAH may not be appropriate for patients aged over 65 years. Even though older patients tend to be diagnosed with more advanced symptoms, and evidence suggests that they are less responsive to PAH-specific therapies, treatment is often less aggressive than in younger patients. Even after adjusting for age, survival rates remain disproportionately lower in the older vs. younger PAH populations. Specific guidelines for diagnosis and treatment of older patients with PAH are needed to improve care and outcomes in this growing population. This review aims to assess the challenges associated with diagnosing and managing PAH in older patients, based on literature searches, authors’ experiences, and expert opinions.